Following the Online Trail of Ukrainian Refugees through Google Trends - Joop Adema; Maitreyee Guha; Joop Age Harm Adema (CESifo Forum, 2022)
Online search behavior offers unique insights about human behavior, not only giving insights about people's state of mind or needs, but also giving insights about their location and mobility intentions. In times of a refugee crisis, such information is important for human well-being in the short run but can also guide integration policies in the long run. Google Trends enables tracking the location, needs, and plans of Ukrainian refugees that left their home country following the invasion of the Russian army. As official statistics and surveys lack granularity and are published with delay, online search data is a valuable addition in humanitarian crises. In this article, we document several use cases of online search data to the current refugee crisis.
Keywords: 330